Lung Functional and Biologic Responses to Variable Ventilation in Experimental Pulmonary and Extrapulmonary Acute Respiratory Distress Syndrome. Issue 7 (July 2016) - Samary, Cynthia S.; Moraes, Lillian; Santos, Cintia L.; Huhle, Robert; Santos, Raquel S.; Ornellas, Debora S.; Felix, Nathane S.; Capelozzi, Vera L.; Schanaider, Alberto; Pelosi, Paolo; de Abreu, Marcelo Gama; Rocco, Patricia R. M.; et al.
Abstract : Objectives: The biologic effects of variable ventilation may depend on the etiology of acute respiratory distress syndrome. We compared variable and conventional ventilation in experimental pulmonary and extrapulmonary acute respiratory distress syndrome. Design: Prospective, randomized, controlled experimental study. Settings: University research laboratory. Subjects: Twenty-four Wistar rats. Interventions: Acute respiratory distress syndrome was induced by Escherichia coli lipopolysaccharide administered intratracheally (pulmonary acute respiratory distress syndrome, n = 12) or intraperitoneally (extrapulmonary acute respiratory distress syndrome, n = 12). After 24 hours, animals were randomly assigned to receive conventional (volume-controlled ventilation, n = 6) or variable ventilation ( n = 6). Nonventilated animals ( n = 4 per etiology) were used for comparison of diffuse alveolar damage, E-cadherin, and molecular biology variables. Variable ventilation was applied on a breath-to-breath basis as a sequence of randomly generated tidal volume values ( n = 600; mean tidal volume = 6 mL/kg), with a 30% coefficient of variation (normal distribution). After randomization, animals were ventilated for 1 hour and lungs were removed for histology and molecular biology analysis. Measurements and Main Results: Variable ventilation improved oxygenation and reduced lung elastance compared with volume-controlled ventilation in both acute respiratory distress syndrome etiologies. In pulmonary acute respiratory distress syndrome, but not in extrapulmonary acute respiratory distress syndrome, variable ventilation 1) decreased total diffuse alveolar damage (median [interquartile range]: volume-controlled ventilation, 12 [11–17] vs variable ventilation, 9 [8–10]; p < 0.01), interleukin-6 expression (volume-controlled ventilation, 21.5 [18.3–23.3] vs variable ventilation, 5.6 [4.6–12.1]; p < 0.001), and angiopoietin-2/angiopoietin-1 ratio (volume-controlled ventilation, 2.0 [1.3–2.1] vs variable ventilation, 0.7 [0.6–1.4]; p < 0.05) and increased relative angiopoietin-1 expression (volume-controlled ventilation, 0.3 [0.2–0.5] vs variable ventilation, 0.8 [0.5–1.3]; p < 0.01). In extrapulmonary acute respiratory distress syndrome, only volume-controlled ventilation increased vascular cell adhesion molecule-1 messenger RNA expression (volume-controlled ventilation, 7.7 [5.7–18.6] vs nonventilated, 0.9 [0.7–1.3]; p < 0.05). E-cadherin expression in lung tissue was reduced in volume-controlled ventilation compared with nonventilated regardless of acute respiratory distress syndrome etiology. In pulmonary acute respiratory distress syndrome, E-cadherin expression was similar in volume-controlled ventilation and variable ventilation; in extrapulmonary acute respiratory distress syndrome, however, it was higher in variable ventilation than in volume-controlled ventilation. Conclusions: Variable ventilation improved lung function in both pulmonary acute respiratory distress syndrome and extrapulmonary acute respiratory distress syndrome. Variable ventilation led to more pronounced beneficial effects in biologic marker expressions in pulmonary acute respiratory distress syndrome compared with extrapulmonary acute respiratory distress syndrome but preserved E-cadherin in lung tissue only in extrapulmonary acute respiratory distress syndrome, thus suggesting lower damage to epithelial cells.